Intellectual Humility and Organizational Forgiveness of University Leaders: A Case of Iraq - AL-ABEDI, ALI RAZZAQ CHYAD; KHDAIR, WAMEEDH A.; AL-HADRAWI, BAQER KHUDAIR ABDUL ABBAS (The journal of contemporary issues in business and government, 2021)
The goal of this study is to explore the intellectual humility of leaders at the University leaders and how it contributes to organizational forgiveness. The paper adopts a descriptive- analytical approach to achieve this goal. As a result, the questionnaire was used as the primary research tool. A random sample of 300 teachers was given out. The statistical analysis was carried out with the program (SPSS V. 20), and the findings revealed that the intellectual humility variable had a general arithmetic mean of (3.87). General arithmetic mean was calculated for the regulatory Forgiveness variable (3.88). The study's findings revealed a link between intellectual humility and organizational forgiveness, as well as an effect of intellectual humility on organizational forgiveness. Work to raise leaders' awareness of the importance of intellectual humility and its role in the promotion of organizational Forgiveness at the University of Kufa. Tolerance is an important factor in the constructive university leadership. To sum up, this outcome, our results on university leadership and innovative behavior in the Iraqi academic environment will enhance both the body of knowledge and the practice of positive psychology. by laying the groundwork for the conceptual and empirical foundations for the concept of positive psychology in organizations, our research may help management and higher education both better understand how it serves as an important internal mechanism.